Efektifitas bahan ajar flipbook IPA berbantuan articulate storyline 3 pada siswa kelas VI di kecamatan pecangaan - Heni Lestari (COLLASE (Creative of Learning Students Elementary Education), 2023)
The purpose of this study is to analyze the effectiveness of science flipbook teaching materials assisted by articulate storyline 3 for sixth grade students in Pecangaan District. This research belongs to the type of Research and Development (R&D) research, namely research related to product development, through the planning, production and evaluation process of the validity of the products that have been produced, with the product to be produced in the form of science flipbook teaching materials assisted by an articulate storyline3. The data analysis technique used the analysis of the acquisition of the t test to determine the effectiveness of the teaching materials developed. Data on the effectiveness of science flipbook teaching materials assisted by articulate storyline 3 were analyzed by gain test, t test at a significance level of 0.05. The product trial design used a pretest posttest control group design for Class VI students at SDN 3 Krasak as the experimental class and students at SDN 1 Lebuawu as the control class. The effective use of science flipbooks is proven by an increase in learning outcomes. The average percentage of prettest in the control and experimental classes is almost the same, namely 61.57 and 58.80. After being given the intervention, the average posttest of the control and experimental classes increased to 78.15 and 87.80. The results of the t-test obtained t-value = 3.346 with a significance level of 0.000 < = 0.05. The conclusion obtained is that the development of science flipbook teaching materials assisted by articulate storyline 3 has proven to be effective for use in learning in class VI SD. It is recommended that teachers use science flipbook teaching materials in learning because they can improve student learning outcomes.